Infections complicating severe alcoholic hepatitis: Enterococcus species represent the most frequently identified pathogen. (2nd July 2016) - Beisel, Claudia; Blessin, Usha; Schulze Zur Wiesch, Julian; Wehmeyer, Malte H.; Lohse, Ansgar W.; Benten, Daniel; Kluwe, Johannes
Abstract: Background: Patients with acute alcoholic steatohepatitis are at a high risk for infections. To date, neither disease-specific pathogen patterns, nor typical sites of infection, nor antibiotic treatment strategies have been established for AH. Aims: To characterize incidence of infections, pathogen spectrum, sites of infection, and related mortality of patients with AH under steroid therapy. Methods: We retrospectively analyzed clinical data of 73 patients with severe alcoholic hepatitis (MELD ≥ 20). Results: Infections were detected in 45 patients (73%). Patients who developed an infection after initiation of corticosteroid therapy had a higher 6-month mortality than patients without onset of infection after initiation of corticosteroid treatment (44% versus 24%, p = 0.116). The pathogen identified most frequently was Enterococcus species. Discussion: Infections frequently complicate severe alcoholic hepatitis and affect survival. The high rate of Enterococcus infections suggests that commonly used antibiotics, such as cephalosporins and quinolones, may represent an ineffective choice of empiric antibiotic treatment for complicated AH.